Profiles of hemolymph antioxidant system in apparently healthy marine bivalve, Perna viridis (Linnaeus, 1758) residing in a normoxic coastal ecosystem. (5th November 2021) - Neethu, B.R.; Reshma, K.J.; Sumithra, T.G.; Akhitha, M.B.; Amala, P.V.; Ratheesh Kumar, R.; Soni, K.B.; Sanil, N.K.
Abstract: Dynamic interactions existing between antioxidant systems (AOS) and residing environment of marine bivalves makes practical relevance in assessing AOS of these animals for ecodiagnostics of residing water and culture practices. Among marine bivalves, Perna viridis act as an ideal aquaculture candidate and plays a pivotal role in ecomonitoring studies. Therefore, the present study was targeted to understand the responses of AOS in haemolymph of P. viridis based on their residing environmental characteristics (salinity, temperature, pH and dissolved oxygen[DO]) in a normoxic coastal environment. Results showed that profiles of all studied AOS components namely, GSH (reduced glutathione) level, GPx (glutathione peroxidase) activity and SOD (superoxide dismutase) activity, were highly influenced by inhabiting conditions, and synchronised action of these AOS maintained comparatively stable levels of oxidative metabolism in haemolymph of P. viridis . However, a uniform correlation between the studied components could not be observed, suggesting variations of AOS levels in natural ecosystem could not be attributed to single environmental factor. Accordingly, linear mixed model analysis combining predicted and unknown influences was carried out and the results indicated that GSH levels have the potential to be used as an early biomarker in P. viridis for fluctuations in DO levels of residing environment, within normoxic conditions. In short, results of present research fetch its application in domestication, culture practices, climate change research and biomonitoring studies. Highlights: First report on linking P. viridis antioxidant profiles with hydrographic conditions Features haemolymph antioxidant profiles in normoxic coastal environment Synchronised action of AOS components maintained stable oxidative metabolism Underlines GSH level as a biomarker for DO fluctuations in normoxic conditions Variations in antioxidant profiles are not attributed by single environmental factor